2013
DOI: 10.1111/sms.12082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between aerobic endurance training and dynamic cerebral blood flow regulation in humans

Abstract: The incidence of orthostatic intolerance is elevated in endurance-trained individuals. We sought to test the hypothesis that aerobic endurance training is associated with an attenuated control of the cerebral vasculature. Endurance trained (ET, n = 13) and age-matched untrained (UT, n = 11) individuals (peak O2 consumption, mean ± SEM; 63 ± 1 vs 42 ± 1 mL/min/kg, P < 0.05) were examined while supine and seated upright. Dynamic cerebral autoregulation (CA) was assessed by calculation of the rate of regulation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
4
25
1
Order By: Relevance
“…Our finding of no difference in dCA between endurance and sedentary is consistent with results from others using repeated sit–stand manoeuvres (Aengevaeren et al., ) and bilateral thigh cuff release in the upright position (Ichikawa et al., ). However, some authors have reported an increased gain and normalized gain during forced oscillations in MAP produced by repeated squat–stand manoeuvres (Labrecque et al., ) and bilateral thigh cuff release, respectively (Lind‐Holst et al., ) – indicative of a reduced damping ability of the cerebral circulation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding of no difference in dCA between endurance and sedentary is consistent with results from others using repeated sit–stand manoeuvres (Aengevaeren et al., ) and bilateral thigh cuff release in the upright position (Ichikawa et al., ). However, some authors have reported an increased gain and normalized gain during forced oscillations in MAP produced by repeated squat–stand manoeuvres (Labrecque et al., ) and bilateral thigh cuff release, respectively (Lind‐Holst et al., ) – indicative of a reduced damping ability of the cerebral circulation.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison to healthy sedentary individuals, endurance‐trained individuals demonstrate larger decreases in MAP, MCAv and cerebral oxygenation during upright thigh cuff release (Ichikawa et al., ) and are more prone to syncope (Levine et al., ) – indicating reduced dCA in endurance athletes during hypotensive challenges. However, Ichikawa et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, an acute hypotension-induced large drop in CBF does not cause syncope even with perfusion pressure below the lower end of the cerebral autoregulation curve (Carey et al 2001b;Ogoh et al 2008Ogoh et al , 2010. In addition, dynamic cerebral autoregulation, one of the CBF regulatory mechanisms, is well preserved in patients with syncope (Carey et al 2001b) and in highly fit athletes who are experiencing orthostatic intolerance (Ichikawa et al 2013). Carbon dioxide levels and indices of cerebrovascular resistance decrease during presyncope, but presyncopal cerebrovascular changes appear to be similar in patients with recurrent vasovagal syncope and in subjects with no previous syncopal symptoms (Carey et al 2001a).…”
Section: Introductionmentioning
confidence: 99%